Preparation and formula optimization method of bentonite-based functional material for moisture storage and bacteria removal
Patent Information
- Application Number
- CN202611068236.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-17
- Publication Date
- 2026-10-20
AI Technical Summary
[0006]本发明的目的是提供一种蓄湿与除菌的膨润土基功能型材料制备及配方优化方法,以解决现有技术中膨润土基功能型材料制备中因缺乏系统理论指导而导致的蓄湿与除菌性能难以协同优化、配方筛选效率低的问题
[0029]与现有技术相比,本发明提供的一种蓄湿与除菌的膨润土基功能型材料制备及配方优化方法,首次将火积理论系统应用于膨润土基蓄湿除菌功能型材料的配方优化中,以总火积耗散率最小化为优化目标,从传质过程不可逆性分析的层面指导材料设计,克服了传统经验试错法效率低、缺乏理论依据的缺陷,为功能型复合材料的设计提供了一种全新的理论框架。
Smart Images

Figure FT_1 
Figure SMS_24
Abstract
Description
Technical Field
[0001] This invention relates to material formulation optimization technology, specifically to a method for preparing and optimizing the formulation of a bentonite-based functional material with moisture retention and sterilization properties. Background Technology
[0002] With the improvement of people's living standards and increasing attention to indoor environmental health, indoor air quality (IAQ) has become an important research topic in the field of building environmental science. Indoor humidity is a key environmental parameter affecting living comfort, human health, and the durability of building materials. Studies have shown that when indoor relative humidity is too high, mold and bacteria easily grow on walls, floors, and furniture surfaces, which not only accelerates material deterioration but may also induce respiratory diseases and allergic reactions; while excessively low humidity can lead to dry skin, static electricity accumulation, and increase the risk of virus transmission in the air. In addition, the air conditioning energy consumption of hospital-type public buildings is significantly higher than that of general public buildings, with fresh air cooling load and personnel cooling load accounting for 40% to 50% of the total air conditioning load. To control nosocomial infections, a large amount of fresh air treated with dehumidification and sterilization needs to be introduced, further increasing operating energy consumption. Therefore, developing building materials that combine passive humidity control and antibacterial and sterilization functions is of great significance for reducing building air conditioning energy consumption and creating a healthy indoor environment.
[0003] Bentonite is a natural clay mineral with montmorillonite as its main mineral component. It possesses a unique layered nanostructure, extremely high specific surface area, and excellent cation exchange capacity. Bentonite can expand 10 to 30 times its volume upon contact with water, and can adsorb 5 to 15 times its own weight in water, exhibiting remarkable moisture absorption and retention capabilities. Furthermore, due to the presence of exchangeable cations between its layers, bentonite can be loaded with antibacterial metal ions such as silver, copper, and zinc through ion exchange, thus endowing the material with broad-spectrum antibacterial properties. However, existing methods for preparing bentonite-based functional materials largely rely on empirical trial-and-error approaches, lacking systematic theoretical guidance to optimize material formulations and microstructures. This leads to a trade-off between moisture retention and antibacterial properties—high moisture absorption capacity is often accompanied by low antibacterial ion loading efficiency and slow desiccation rate, making it difficult to achieve optimal synergy between the two functions.
[0004] Entransy theory is a novel method for analyzing heat and mass transfer that has emerged in recent years. Unlike traditional entropy analysis, entransy describes the ability of a substance to transfer heat, and its dissipation quantifies irreversible losses during heat transfer. In recent years, researchers have extended entransy theory to the field of mass transfer, proposing concepts such as moisture entransy to describe the mass transfer capacity and irreversible losses during moisture transfer. Existing research has shown that the principle of minimizing heat resistance through entransy dissipation can be used to optimize heat and mass transfer processes, providing new theoretical tools for material microstructure design and formulation optimization.
[0005] Currently, there are no patents or literature reports that systematically apply the fire accumulation theory to the formulation optimization and preparation guidance of bentonite-based moisture-retaining and antibacterial functional materials. Summary of the Invention
[0006] The purpose of this invention is to provide a method for preparing and optimizing the formulation of bentonite-based functional materials with moisture retention and sterilization properties, in order to solve the problems in the preparation of bentonite-based functional materials in the prior art, which are difficult to optimize the moisture retention and sterilization properties in a coordinated manner and have low formulation screening efficiency due to the lack of systematic theoretical guidance.
[0007] To achieve the above objectives, the present invention provides the following technical solution:
[0008] In a first aspect, the present invention provides a method for preparing and optimizing the formulation of a bentonite-based functional material with moisture retention and sterilization properties, comprising the following steps:
[0009] Step 1: Establish a pyrolysis analysis model for bentonite-based functional materials, with the goal of minimizing the total pyrolysis dissipation rate, and determine the theoretical optimization range of the material formulation.
[0010] Step 2: Based on the theoretical optimization range, prepare bentonite-based materials loaded with metal ions;
[0011] Step 3: Conduct a pyrolysis dissipation rate experiment on the bentonite-based material prepared in Step 2 to verify the actual pyrolysis dissipation rate.
[0012] Step 4: Compare the actual fire accumulation dissipation rate with the theoretical minimum fire accumulation dissipation rate determined in Step 1. When the relative deviation between the two exceeds a preset threshold, adjust the preparation process parameters in Step 2 and repeat Step 2 to Step 3 until the relative deviation between the actual fire accumulation dissipation rate and the theoretical minimum fire accumulation dissipation rate is less than the preset threshold, thus completing the preparation and formula optimization.
[0013] Furthermore, the establishment of the pyrochemical analysis model for bentonite-based functional materials in step one specifically includes the following sub-steps:
[0014] (1) The moisture transfer process of bentonite-based materials during the moisture absorption and release process is regarded as a one-dimensional unsteady mass transfer process, and the moisture transfer mass flow density inside the material is defined. In the formula The apparent density of the material, The specific volume of water in the material. Temperature is the temperature at which the chemical potential for water transfer is located. This represents the rate of water diffusion.
[0015] (2) Define the total heat dissipation rate of a material in a complete moisture absorption-desorption cycle. In the formula It is a moisture absorption-desorption cycle. To control the volume of the material;
[0016] (3) With minimizing the total fire accumulation dissipation rate as the optimization objective, a multi-objective constrained optimization function for bentonite-based functional materials is established: ,in Silver ion loading, Porosity of the material The average pore size of the material. This refers to the interlayer spacing of the material.
[0017] Furthermore, the preset threshold in step four is: when If necessary, adjust the preparation process parameters in step two and repeat the operation; until... The preparation and formulation optimization were completed; among them This represents the actual fire accumulation dissipation rate. This represents the theoretical minimum pyrolysis rate.
[0018] Furthermore, the preparation process parameters are at least one of the following: metal ion solution concentration, ion exchange reaction temperature, and ion exchange reaction time.
[0019] Secondly, the present invention provides a bentonite-based functional material optimized by the method described above, comprising a bentonite matrix and silver ions loaded between bentonite layers, wherein the silver ion loading is 0.8wt% to 2.5wt%, the porosity of the material is 45% to 70%, the average pore size is 5nm to 25nm, the interlayer spacing is 1.5nm to 3.2nm, and the relative deviation between the actual pyrolysis dissipation rate of the material and the theoretical minimum pyrolysis dissipation rate under the same conditions is less than 5%.
[0020] Thirdly, the present invention provides a method for preparing bentonite-based functional materials as described above, comprising the following steps:
[0021] S1. The calcium-based bentonite ore is crushed and sieved. Bentonite powder with a particle size of less than 200 mesh is dried and dispersed in deionized water. An activator is added for activation treatment to obtain an activated modified bentonite matrix.
[0022] S2. The activated and modified bentonite matrix is dispersed in a solution containing metal ions to carry out an ion exchange reaction, so that the metal ions are loaded between the bentonite layers.
[0023] S3. Separate, wash, dry, grind, and sieve to obtain the bentonite-based functional material.
[0024] Further, the activator is a hydrogen peroxide solution, the mass fraction of the hydrogen peroxide solution is 5% to 15%, the amount added is 0.5 to 2.0 times the mass of the bentonite powder, the activation treatment temperature is 40 to 60°C, and the reaction time is 1 to 3 hours;
[0025] The solution containing metal ions is a silver ammonia complex solution, which is prepared by adjusting the pH of a 0.01-0.05 mol / L silver nitrate solution to 9.0-10.5 with ammonia. The solid-liquid ratio of the activated modified bentonite matrix to the silver ammonia complex solution is 1:10-1:20, the ion exchange reaction temperature is 40-60℃, and the reaction time is 4-8 hours.
[0026] Fourthly, the present invention provides the application of the bentonite-based functional material described above in the preparation of humidity-regulating coatings for building interior walls or antibacterial coatings for air conditioning heat exchangers.
[0027] Fifthly, the present invention provides a moisture-retaining and antibacterial functional layer for building interior walls, comprising the bentonite-based functional material described above, and a building interior wall base material, wherein the mass ratio of the bentonite-based functional material to the building interior wall base material is 15:85 to 40:60, and the coating thickness of the functional layer is 2 to 5 mm.
[0028] Furthermore, the building interior wall base material is any one of water-based acrylic paint, diatomaceous earth paint, cement-based putty, or gypsum-based putty.
[0029] Compared with existing technologies, the present invention provides a method for preparing and optimizing the formulation of bentonite-based functional materials with moisture retention and sterilization. For the first time, the pyrolysis theory is systematically applied to the formulation optimization of bentonite-based moisture retention and sterilization functional materials. With minimizing the total pyrolysis dissipation rate as the optimization objective, the method guides material design from the perspective of irreversible mass transfer process analysis. It overcomes the shortcomings of traditional empirical trial-and-error methods, such as low efficiency and lack of theoretical basis, and provides a brand-new theoretical framework for the design of functional composite materials.
[0030] This invention establishes a multi-objective constrained optimization function to quantitatively determine the theoretical optimization range of key formulation parameters such as silver ion loading, porosity, average pore size, and interlayer spacing, thereby achieving synergistic optimization of moisture retention and sterilization performance and avoiding performance conflicts between the two.
[0031] This invention establishes an experimental verification and iterative optimization mechanism for fire accumulation dissipation rate. By comparing experimental test results with theoretical targets, closed-loop optimization of material formulation is achieved, ensuring the controllability and stability of the final product performance.
[0032] The bentonite-based functional material prepared by the method of this invention can be directly used in the preparation of a moisture-retaining and antibacterial functional layer for building interior walls or an antibacterial coating for the surface of air conditioning heat exchangers. It can achieve passive indoor humidity control and bacterial inhibition without additional energy consumption, and has the characteristics of energy saving, environmental protection, green and healthy. Attached Figure Description
[0033] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in this invention. For those skilled in the art, other drawings can be obtained based on these drawings.
[0034] Figure 1 A flowchart illustrating the method steps provided in an embodiment of the present invention. Detailed Implementation
[0035] To enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings.
[0036] As attached Figure 1 As shown:
[0037] Example 1:
[0038] This invention provides a method for preparing and optimizing the formulation of bentonite-based functional materials with moisture retention and sterilization properties. The specific steps are as follows.
[0039] Step 1: Establish a fire accumulation analysis model and determine the theoretical optimization range of the formula.
[0040] A pyrophoretic analysis model for bentonite-based functional materials is established. The moisture transfer during the material's moisture absorption and release processes is considered a one-dimensional unsteady-state mass transfer process, and the moisture transfer pyrophoretic flux density is defined. Define the total heat dissipation rate of a material during a complete moisture absorption-desorption cycle τ (τ=24h). Minimize as the optimization objective, and establish a multi-objective constrained optimization function. The constraints are .
[0041] A genetic algorithm was used to solve the above multi-objective constrained optimization function. The parameters of the genetic algorithm were set as follows: population size 100, real number encoding, tournament selection (tournament size 2), simulated binary crossover (crossover probability 0.9), polynomial mutation (mutation probability 0.1), elitist strategy retaining the top 10% of optimal solutions, and termination condition: 500 generations or fitness change less than 1 × 10⁻⁶. -6The theoretical optimal values for silver ion loading, porosity, average pore size, and interlayer spacing were determined to be 1.5 wt%, 58%, 12 nm, and 2.1 nm, respectively, corresponding to the theoretical minimum fire accumulation dissipation rate. 0.315 J / (m 3 ·s).
[0042] Step 2: Preparation of hydrogen peroxide-activated modified bentonite matrix
[0043] Take calcium-based bentonite ore (montmorillonite content ≥75%), crush it in a pulverizer, and then sieve it using a standard sieve to obtain bentonite powder with a particle size of less than 200 mesh. Place the obtained powder in a forced-air drying oven and dry it at 105℃ for 4 hours to obtain dried bentonite powder.
[0044] Weigh 50g of dried bentonite powder and disperse it in 500mL of deionized water at a mass ratio of 1:10. Place the mixture on a constant temperature magnetic stirrer and stir at 400rpm for 1.5 hours at room temperature to obtain a uniform bentonite suspension.
[0045] Add 60 mL of a 10% hydrogen peroxide solution (the amount of hydrogen peroxide solution added is 1.2 times the mass of the bentonite powder) to the above bentonite suspension. Place the suspension in a water bath and stir at 300 rpm for 2 hours at 50°C. During the reaction, hydrogen peroxide decomposes to produce oxygen, which enhances the dispersibility of bentonite minerals and the regularity of their interlayer structure through oxidation.
[0046] After the reaction was complete, the suspension was transferred to a centrifuge tube and centrifuged at 4000 rpm for 10 minutes, discarding the supernatant. The resulting precipitate was repeatedly washed and centrifuged with deionized water until the pH of the supernatant reached 7.0. The resulting filter cake was placed in a forced-air drying oven and dried at 105°C for 10 hours. The dried solid product was ground in a mortar and passed through a 200-mesh standard sieve to obtain the hydrogen peroxide-activated modified bentonite matrix.
[0047] Step 3: Preparation of bentonite-based composite materials by silver ion loading
[0048] Prepare 200 mL of a 0.03 mol / L silver nitrate solution in a brown reagent bottle. Under stirring, add 25% ammonia solution dropwise, monitoring the pH change with a precision pH meter until the solution pH reaches 10.0, thus obtaining the silver ammonia complex ion solution ([Ag(NH3)2)). + The silver ammonia complex solution is colorless and transparent.
[0049] Take 10g of the hydrogen peroxide-activated modified bentonite matrix obtained in step two and disperse it in 200mL of silver ammonia complex ion solution at a solid-liquid ratio of 1:20. Place the mixture in a water bath and react it at 300rpm for 6 hours at 50℃ under light-protected conditions (using aluminum foil to wrap the reaction vessel). Silver ions are introduced into the bentonite interlayer through the ion exchange reaction between the exchangeable cations in the bentonite interlayer and the silver ammonia complex ions.
[0050] After the reaction, the suspension was transferred to a centrifuge tube and centrifuged at 4000 rpm for 10 minutes, discarding the supernatant. The resulting precipitate was repeatedly washed and centrifuged with deionized water until no chloride ions were detected in the washing liquid (tested with 0.1 mol / L AgNO3 solution; if no white precipitate was formed, chloride ions were considered absent). The obtained solid product was placed in a vacuum drying oven and vacuum dried at 60°C for 18 hours. The dried solid product was ground in a mortar and pestle and passed through a 200-mesh standard sieve to obtain the moisture-retaining and antibacterial dual-functional bentonite-based composite material.
[0051] The obtained composite material was characterized as follows: Inductively coupled plasma atomic emission spectrometry (ICP-AES) was used to determine the silver ion loading. The silver ion loading in the composite material prepared in this embodiment was found to be 1.52 wt%, with a relative deviation of 1.3% from the theoretical optimum of 1.5 wt% determined in step one. The pore structure parameters of the material were determined using nitrogen adsorption-desorption. The specific surface area was calculated according to the BET multilayer adsorption theory, and the pore size distribution was calculated according to the Barrett-Joyner-Halenda (BJH) method. The measured BET specific surface area of the material was 186.5 m². 2 / g, porosity 59.2%, average pore size 11.8nm. Interlayer spacing was determined by X-ray diffraction, based on Bragg's equation. The interlayer spacing was calculated and measured to be 2.08 nm. All the above parameters fall within the theoretical optimization range determined in step one.
[0052] Step 4: Experimental Verification of Fire Accumulation Dissipation Rate
[0053] The bentonite-based composite material prepared in step three was placed in a constant temperature and humidity chamber for a moisture absorption-desorption cycle experiment. The test conditions were: temperature 25℃±1℃, relative humidity cyclically changing between 30%RH and 90%RH (the specific procedure was: relative humidity increased from 30%RH to 90%RH at a rate of 5%RH / hour, maintained at 90%RH for 4 hours, then decreased to 30%RH at a rate of 5%RH / hour, and maintained at 30%RH for 4 hours), with a cycle period of 24 hours, for a total of 5 cycles.
[0054] A dynamic moisture adsorption analyzer was used to record the amount of moisture adsorbed and desorbed by the material in real time during the moisture absorption-desorption cycle. Based on the test data, the actual fire accumulation dissipation rate of the material was calculated according to the following formula:
[0055]
[0056] In the formula, and These represent the amount of moisture absorbed and released during the i-th time step (time step set to 1 minute), respectively. and These are the corresponding enthalpy of moisture absorption and enthalpy of moisture release (measured in real time using the equal adsorption heat measurement module of the dynamic moisture adsorption analyzer), and τ is the cycle period (24 hours).
[0057] The actual pyrolysis dissipation rate of the composite material in this embodiment was calculated. .
[0058] Actual pyrophoric dissipation rate The theoretical minimum pyroclastic dissipation rate determined in step one Compare and calculate the relative deviation:
[0059]
[0060] The relative deviation is 3.8%, which is less than the preset threshold of 5%, indicating that the current formula and preparation process have met the optimization requirements and no iterative adjustments are needed.
[0061] Step 5: Preparation of the moisture-retaining and sterilization functional layer of the building's interior walls
[0062] Take 100g of the optimized bentonite-based functional material from step four and mix it with 400g of commercially available water-based acrylic interior wall coating (the mass ratio of bentonite-based functional material to building interior wall coating is 20:80). Place the mixture in a disperser and stir and disperse it at 600rpm for 30 minutes to obtain a moisture-retaining and antibacterial functional coating.
[0063] The obtained functional coating was evenly applied to the cement mortar base wall using a scraper application method. The wet film thickness was controlled with a scraper, and two coats were applied with a 4-hour interval between each coat. The final dry film thickness was 3 mm. After coating, the coating was allowed to cure naturally at room temperature for 7 days to obtain the moisture-retaining and antibacterial functional layer for the building's interior wall.
[0064] Performance testing:
[0065] (1) Moisture storage performance test
[0066] The functional layer test block (100mm×100mm×10mm, with a functional layer thickness of 3mm) was placed in a constant temperature and humidity chamber and allowed to absorb moisture for 24 hours at 25℃ and 90% relative humidity. The mass change of the test block before and after moisture absorption was measured using a precision electronic balance (accuracy 0.0001g), and the saturated moisture absorption was calculated. The measured saturated moisture absorption was 286g / m³. 2 .
[0067] The saturated test block was placed in a constant temperature and humidity chamber and allowed to dehumidify for 24 hours at 25℃ and 30% relative humidity. The mass change of the test block before and after dehumidification was measured, and the amount of moisture released was calculated to be 253 g / m³. 2 The moisture release rate (moisture release / moisture absorption × 100%) is 88.5%, indicating that the functional layer has excellent moisture absorption-moisture release reversible performance.
[0068] (2) Sterilization performance test
[0069] The test was conducted according to GB / T21866-2008 "Determination of Antibacterial Properties and Antibacterial Effects of Antibacterial Coatings (Films)". Test blocks (50mm × 50mm) coated with the functional layer were inoculated with Staphylococcus aureus (ATCC6538) and Escherichia coli (ATCC8739) bacterial suspensions, respectively, with a suspension concentration of 1 × 10⁻⁶. 6 The inoculum concentration was CFU / mL, and the inoculum volume was 0.2 mL. The inoculated test pieces were placed in petri dishes and incubated for 24 hours at 35°C and 90% relative humidity. After incubation, surviving bacteria on the surface of the test pieces were eluted with phosphate buffer. The eluent was serially diluted and spread onto nutrient agar plates, incubated at 35°C for 24 hours, and the number of surviving colonies was counted to calculate the inhibition rate.
[0070] Antibacterial rate = (Number of surviving bacteria in control sample - Number of surviving bacteria in test sample) / Number of surviving bacteria in control sample × 100%.
[0071] The results showed that the functional layer prepared in this embodiment had an inhibition rate of 99.7% against Staphylococcus aureus and 99.4% against Escherichia coli, exhibiting excellent broad-spectrum antibacterial properties.
[0072] Example 2:
[0073] This embodiment is basically the same as Embodiment 1, except that in this embodiment, the mass fraction of hydrogen peroxide solution is 8%, the amount of hydrogen peroxide solution added is 1.5 times the mass of bentonite powder, the activation treatment temperature is 45°C, and the activation treatment reaction time is 2.5 hours. The remaining steps are the same as in Embodiment 1.
[0074] Testing showed that the composite material prepared in this embodiment had a silver ion loading of 1.48 wt% and a BET specific surface area of 179.3 m².2 The material has a porosity of 57.6%, an average pore size of 12.4 nm, and an interlayer spacing of 2.05 nm. All of these parameters fall within the theoretical optimization range determined in step one.
[0075] The flame dissipation rate was verified by conducting an experimental test according to step four of Example 1, and the actual flame dissipation rate of the composite material in this example was calculated. The actual pyrophoric dissipation rate is compared with the theoretical minimum pyrophoric dissipation rate. The relative deviation is as follows:
[0076]
[0077] The relative deviation was 8.3%, which is greater than 5% but less than 10%, and did not reach the threshold (10%) for initiating iterative optimization. However, in order to further improve the material properties, one iterative optimization was still performed.
[0078] Iterative optimization: In step three, the concentration of the silver nitrate solution was adjusted from 0.03 mol / L to 0.035 mol / L, and the ion exchange reaction time was extended from 6 hours to 7 hours, while keeping other conditions unchanged. Steps three and four were repeated.
[0079] After iterative optimization, the prepared composite material had a silver ion loading of 1.63 wt%, a porosity of 58.4%, an average pore size of 11.9 nm, and an interlayer spacing of 2.10 nm. The pyrolysis dissipation rate was then re-verified through experiments, and the actual pyrolysis dissipation rate was calculated. The relative deviation is:
[0080]
[0081] The relative deviation was reduced to 4.4%, which is less than 5%, meeting the optimization requirements.
[0082] A moisture-retaining and antibacterial functional layer for building interior walls was prepared according to the method in Example 1, and its performance was tested. The results showed that the saturated moisture absorption of the functional layer at 25°C and 90% relative humidity was 274 g / m². 2 The moisture release rate at 25℃ and 30% relative humidity is 236 g / m³. 2 The moisture release rate was 86.2%. The inhibition rate against Staphylococcus aureus was 99.5%, and the inhibition rate against Escherichia coli was 99.3%.
[0083] Example 3:
[0084] This embodiment is basically the same as Embodiment 1, except that in this embodiment, the concentration of silver nitrate solution is 0.02 mol / L, the pH of silver ammonia complex ion solution is 9.5, the ion exchange reaction temperature is 45℃, the ion exchange reaction time is 8 hours, and the remaining steps are the same as in Embodiment 1.
[0085] Testing showed that the composite material prepared in this embodiment had a silver ion loading of 1.03 wt% and a BET specific surface area of 192.4 m². 2 The material has a porosity of 61.2%, an average pore size of 11.2 nm, and an interlayer spacing of 2.12 nm. All of these parameters fall within the theoretical optimization range determined in step one.
[0086] The flame dissipation rate was verified by conducting an experimental test according to step four of Example 1, and the actual flame dissipation rate of the composite material in this example was calculated. The actual pyrophoric dissipation rate is compared with the theoretical minimum pyrophoric dissipation rate. The relative deviation is as follows:
[0087]
[0088] The relative deviation is 11.7%, which is greater than the preset threshold of 10%, and iterative optimization is required.
[0089] Iterative optimization: In step three, the concentration of the silver nitrate solution was adjusted from 0.02 mol / L to 0.028 mol / L, the ion exchange reaction time was shortened from 8 hours to 6 hours, the ion exchange reaction temperature was kept constant at 45℃, and all other conditions remained unchanged. Steps three and four were repeated.
[0090] After iterative optimization, the prepared composite material had a silver ion loading of 1.47 wt%, a porosity of 59.8%, an average pore size of 11.5 nm, and an interlayer spacing of 2.09 nm. The pyrolysis dissipation rate was then re-performed to verify the results, and the actual pyrolysis dissipation rate was calculated. The relative deviation is:
[0091]
[0092] The relative deviation was reduced to 4.1%, which is less than 5%, meeting the optimization requirements.
[0093] A moisture-retaining and antibacterial functional layer for building interior walls was prepared according to the method in Example 1, and its performance was tested. The results showed that the saturated moisture absorption of the functional layer at 25°C and 90% relative humidity was 293 g / m². 2 The moisture release rate at 25℃ and 30% relative humidity is 264 g / m³. 2The moisture release rate was 90.1%. The inhibition rate against Staphylococcus aureus was 98.2%, and the inhibition rate against Escherichia coli was 97.6%.
[0094] Comparative Example 1:
[0095] In this comparative example, natural calcium-based bentonite without hydrogen peroxide activation modification was directly used for silver ion loading, and the remaining steps were the same as in Example 1.
[0096] The specific method is as follows: Take 10g of unactivated calcium-based bentonite ore powder (montmorillonite content ≥75%, particle size below 200 mesh), without hydrogen peroxide activation treatment, and directly carry out an ion exchange reaction with a 0.03mol / L silver ammonia complex ion solution at a solid-liquid ratio of 1:20. The reaction conditions are: temperature 50℃, protection from light, stirring speed 300rpm, and reaction time 6 hours. Subsequent separation, washing, drying, grinding, and sieving steps are the same as step three of Example 1.
[0097] Testing revealed that the silver ion loading of the composite material prepared in this comparative example was only 0.68 wt%, and the BET specific surface area was 98.7 m². 2 / g, with a porosity of 38.5%, an average pore size of 8.6nm, and an interlayer spacing of 1.52nm. The pyrolysis dissipation rate was experimentally verified according to step four of Example 1, and the actual pyrolysis dissipation rate was calculated. With respect to the theoretical minimum pyroclastic dissipation rate The relative deviation is:
[0098]
[0099] The relative deviation was as high as 66.3%, far exceeding the preset threshold of 10%.
[0100] A moisture-retaining and antibacterial functional layer for building interior walls was prepared according to the method in Example 1, and its performance was tested. The results showed that the saturated moisture absorption of the functional layer at 25°C and 90% relative humidity was 187 g / m². 2 The moisture release rate at 25℃ and 30% relative humidity is 135g / m³. 2 The moisture release rate was 72.3%. The inhibition rate against Staphylococcus aureus was 85.6%, and the inhibition rate against Escherichia coli was 83.2%.
[0101] The results of this comparative example show that the bentonite without hydrogen peroxide activation modification has poor dispersibility and interlayer structure regularity, resulting in low silver ion loading efficiency and significantly inferior moisture retention and sterilization performance compared to Examples 1-3. This further verifies the necessity and effectiveness of the hydrogen peroxide activation modification step in this invention.
[0102] Comparative Example 2:
[0103] This comparative example uses the traditional single-factor trial-and-error method for formula optimization without introducing a fire accumulation analysis model, in order to illustrate the superiority of the optimization method based on the fire accumulation analysis model of this invention over the traditional method.
[0104] The specific method is as follows: The silver ion loading of the bentonite-based functional material was prepared at five gradients: 0.5 wt%, 1.0 wt%, 1.5 wt%, 2.0 wt%, and 2.5 wt%. For each gradient, the hydrogen peroxide-activated modified bentonite matrix was prepared according to step two of Example 1. Then, the target silver ion loading was achieved by adjusting the concentration of the silver nitrate solution in step three (0.01 mol / L, 0.02 mol / L, 0.03 mol / L, 0.04 mol / L, and 0.05 mol / L, respectively). The remaining preparation conditions were the same as in Example 1. A total of 5 sets of experiments were required, with each set repeated 3 times, for a total of 15 experiments.
[0105] The moisture retention and sterilization properties of the composite materials prepared in each group of experiments were tested according to the method in Example 1, and the optimal formulation was selected through comprehensive comparison. The tests showed that the composite material with a silver ion loading of 1.5 wt% exhibited the best overall performance, but its porosity was 52.3%, the average pore size was 10.1 nm, and the interlayer spacing was 1.95 nm. The flame dissipation rate was verified by the method in step four of Example 1, and the actual flame dissipation rate was calculated. With respect to the theoretical minimum pyroclastic dissipation rate The relative deviation was 22.2%.
[0106] Compared to Example 1, the experimental cycle of this comparative example was extended by approximately 2.5 times (Example 1 required only one fire accumulation modeling experiment + one verification experiment, for a total of 3 experiments; while Comparative Example 2 required 15 experiments), and the relative deviation between the actual fire accumulation dissipation rate of the final product and the theoretical minimum was significantly higher (3.8% for Example 1 and 22.2% for Comparative Example 2). This indicates that the empirical trial-and-error method without fire accumulation analysis is difficult to achieve true synergistic optimization of material microstructure and mass transfer performance, and the experimental efficiency is low.
[0107] Comparative Example 3:
[0108] In this comparative example, the optimization objective for the fire accumulation was changed from "minimizing the total fire accumulation dissipation rate" to "maximizing the maximum moisture absorption capacity," while the remaining formulation parameters remained the same as in Example 1. That is, the maximum moisture absorption capacity was ≥350 g / m³. 2 To optimize the target, composite materials were prepared by adjusting the preparation process parameters.
[0109] The specific method is as follows: Prepare the hydrogen peroxide-activated modified bentonite matrix according to step two of Example 1. Then, in step three, reduce the concentration of the silver ammonia complex solution (0.015 mol / L) and shorten the ion exchange reaction time (3 hours) to reduce the silver ion loading, thereby obtaining higher porosity and a larger average pore size. The remaining steps are the same as in Example 1.
[0110] Testing revealed that the composite material prepared in this comparative example exhibited a porosity as high as 72.5%, an average pore size of 28.6 nm, an interlayer spacing of 2.45 nm, a silver ion loading of only 0.92 wt%, and a BET specific surface area of 165.3 m². 2 / g. The moisture storage performance was tested according to the method in Example 1, and the saturated moisture absorption capacity at 25°C and 90% relative humidity was 358 g / m³. 2 The optimization target (≥350g / m³) has been achieved. 2 However, when the sterilization performance was tested according to the method in Example 1, the inhibition rate against Staphylococcus aureus was only 91.3%, and the inhibition rate against Escherichia coli was only 89.7%. The actual fire accumulation dissipation rate was calculated by conducting a fire accumulation dissipation rate experiment according to step four of Example 1. With respect to the theoretical minimum pyroclastic dissipation rate The relative deviation is 62.5%.
[0111] The results of this comparative example show that optimizing a single performance index (maximum moisture absorption) leads to excessively developed pores and larger pore sizes in the material. Silver ions are easily lost in the overly open pore structure, resulting in a significant decrease in sterilization performance and an increase in irreversible losses in the overall mass transfer process. This verifies the significant advantages of the strategy of minimizing the total heat accumulation dissipation rate as the multi-objective optimization goal of this invention.
[0112] Example 4:
[0113] This embodiment provides a method for preparing and optimizing the formulation of a bentonite-based functional material with moisture retention and sterilization properties. The difference between this method and Example 1 is that the ratio of the bentonite-based functional material to the building interior wall base material and the type of base material are different in step five.
[0114] In this embodiment, the base material for the building interior wall is diatomaceous earth paint, and the mass ratio of bentonite-based functional material to diatomaceous earth paint is 25:75. The specific operation is as follows: Take 100g of the bentonite-based functional material optimized in step four of Example 1, mix it with 300g of commercially available diatomaceous earth paint, and stir and disperse at 600rpm for 30 minutes to obtain a moisture-retaining and antibacterial functional coating. Apply the obtained functional coating evenly to a cement mortar base wall surface, controlling the coating thickness to 3mm. After natural curing for 7 days, the moisture-retaining and antibacterial functional layer for the building interior wall is obtained.
[0115] Testing showed that the saturated moisture absorption of the functional layer prepared in this embodiment was 312 g / m³ under conditions of 25°C and 90% relative humidity. 2 The moisture release rate at 25℃ and 30% relative humidity is 281g / m³. 2 The moisture release rate is 90.1%. The inhibition rate against Staphylococcus aureus is 99.5%, and the inhibition rate against Escherichia coli is 99.2%.
[0116] This embodiment demonstrates that the bentonite-based functional material of the present invention can be applied to different types of building interior wall base materials, and has good versatility and wide applicability.
[0117] Example 5:
[0118] This embodiment provides the application of a bentonite-based functional material with moisture retention and sterilization properties in a sterilization coating on the surface of an air conditioning heat exchanger.
[0119] Bentonite-based functional materials were prepared and optimized according to steps one through four of Example 1. 100g of the optimized bentonite-based functional material was mixed with 200g of waterborne acrylic resin (mass ratio 33.3:66.7), and an appropriate amount of deionized water was added to adjust the viscosity to 30-40 seconds as measured by a Forte 4 cup viscometer. The mixture was stirred and dispersed at 800 rpm for 45 minutes to obtain an antibacterial coating slurry.
[0120] The above-mentioned antibacterial coating slurry was sprayed onto the surface of the air conditioning heat exchanger (copper tube aluminum fin heat exchanger) using an air spraying method. The spraying pressure was 0.4 MPa, the spraying distance was 20 cm, and the number of sprays was 3, with an interval of 10 minutes between each spray. The final dry film thickness of the coating was 1 mm. After spraying, it was naturally cured at room temperature for 48 hours.
[0121] The antibacterial performance of heat exchanger fins coated with an antibacterial coating was tested according to the method in GB / T21866-2008. The results showed that the inhibition rate against Staphylococcus aureus was 99.6%, and the inhibition rate against Escherichia coli was 99.3%. During the moisture absorption process at 25℃ and with relative humidity increasing from 30%RH to 90%RH, the moisture adsorption capacity of the coating material was 245 g / m³. 2 It exhibits good moisture storage performance, which helps to recover condensate on the surface of air conditioner heat exchangers.
[0122] Industrial applicability:
[0123] The present invention discloses a method for preparing and optimizing the formulation of bentonite-based functional materials with moisture-retaining and antibacterial properties. Based on the theory of pyrolysis, this method achieves scientific optimization and closed-loop iterative optimization of the material formulation. The resulting bentonite-based functional materials possess both excellent moisture-retaining performance and broad-spectrum antibacterial properties. This material can be directly used in the preparation of moisture-retaining and antibacterial functional layers for building interior walls or as antibacterial coatings for air conditioning heat exchangers. It achieves passive indoor humidity control and bacterial inhibition without additional energy consumption, making it suitable for residential buildings, hospitals, schools, museums, and other buildings with high requirements for indoor environmental quality. It exhibits significant energy-saving and environmental protection benefits and promising market application prospects.
[0124] The foregoing has only described certain exemplary embodiments of the present invention by way of illustration. Undoubtedly, those skilled in the art can modify the described embodiments in various ways without departing from the spirit and scope of the present invention. Therefore, the foregoing drawings and descriptions are illustrative in nature and should not be construed as limiting the scope of protection of the claims of the present invention.
Claims
1. A method for preparing and optimizing the formulation of a bentonite-based functional material with moisture-retaining and antibacterial properties, characterized in that, Includes the following steps: Step 1: Establish a pyrolysis analysis model for bentonite-based functional materials, with the goal of minimizing the total pyrolysis dissipation rate, and determine the theoretical optimization range of the material formulation. Step 2: Based on the theoretical optimization range, prepare bentonite-based materials loaded with metal ions; Step 3: Conduct a pyrolysis dissipation rate experiment on the bentonite-based material prepared in Step 2 to verify the actual pyrolysis dissipation rate. Step 4: Compare the actual fire accumulation dissipation rate with the theoretical minimum fire accumulation dissipation rate determined in Step 1. When the relative deviation between the two exceeds a preset threshold, adjust the preparation process parameters in Step 2 and repeat Step 2 to Step 3 until the relative deviation between the actual fire accumulation dissipation rate and the theoretical minimum fire accumulation dissipation rate is less than the preset threshold, thus completing the preparation and formula optimization.
2. The method for preparing and optimizing the formulation of a bentonite-based functional material with moisture retention and sterilization according to claim 1, characterized in that, Step one, which establishes the pyrochemical analysis model for bentonite-based functional materials, specifically includes the following sub-steps: (1) The moisture transfer process of bentonite-based functional materials during the moisture absorption and release process is regarded as a one-dimensional unsteady mass transfer process, and the moisture mass transfer flow density inside the material is defined. In the formula The apparent density of the material, The specific volume of water in the material. Temperature is the temperature at which the chemical potential for water transfer is located. This represents the rate of water diffusion. (2) Define the total heat dissipation rate of a material in a complete moisture absorption-desorption cycle. In the formula It is a moisture absorption-desorption cycle. To control the volume of the material; (3) With minimizing the total fire accumulation dissipation rate as the optimization objective, a multi-objective constrained optimization function for bentonite-based functional materials is established: ,in Silver ion loading, Porosity of the material The average pore size of the material. This refers to the interlayer spacing of the material.
3. The method for preparing and optimizing the formulation of a bentonite-based functional material with moisture retention and sterilization according to claim 1, characterized in that, The preset threshold in step four is: when If necessary, adjust the preparation process parameters in step two and repeat the operation; until... The preparation and formulation optimization were completed; among them This represents the actual fire accumulation dissipation rate. This represents the theoretical minimum pyrolysis rate.
4. The method for preparing and optimizing the formulation of a bentonite-based functional material with moisture retention and sterilization according to claim 1, characterized in that, The preparation process parameters are at least one of the following: metal ion solution concentration, ion exchange reaction temperature, and ion exchange reaction time.
5. A bentonite-based functional material optimized by the method described in any one of claims 1 to 4, characterized in that, The material comprises a bentonite matrix and silver ions loaded between bentonite layers, wherein the silver ion loading is 0.8wt% to 2.5wt%, the porosity of the material is 45% to 70%, the average pore size is 5nm to 25nm, the interlayer spacing is 1.5nm to 3.2nm, and the relative deviation between the actual pyrolysis dissipation rate of the material and the theoretical minimum pyrolysis dissipation rate under the same conditions is less than 5%.
6. A method for preparing a bentonite-based functional material as described in claim 5, characterized in that, Includes the following steps: S1. The calcium-based bentonite ore is crushed and sieved. Bentonite powder with a particle size of less than 200 mesh is dried and dispersed in deionized water. An activator is added for activation treatment to obtain an activated modified bentonite matrix. S2. The activated and modified bentonite matrix is dispersed in a solution containing metal ions to carry out an ion exchange reaction, so that the metal ions are loaded between the bentonite layers. S3. Separate, wash, dry, grind, and sieve to obtain the bentonite-based functional material.
7. The preparation method according to claim 6, characterized in that, The activator is a hydrogen peroxide solution, the mass fraction of which is 5% to 15%, and the amount added is 0.5 to 2.0 times the mass of the bentonite powder. The activation treatment temperature is 40 to 60°C, and the reaction time is 1 to 3 hours. The solution containing metal ions is a silver ammonia complex solution, which is prepared by adjusting the pH of a 0.01-0.05 mol / L silver nitrate solution to 9.0-10.5 with ammonia. The solid-liquid ratio of the activated modified bentonite matrix to the silver ammonia complex solution is 1:10-1:20, the ion exchange reaction temperature is 40-60℃, and the reaction time is 4-8 hours.
8. The application of the bentonite-based functional material according to claim 5 in the preparation of humidity-regulating coatings for building interior walls or antibacterial coatings for air conditioning heat exchangers.
9. A moisture-retaining and antibacterial functional layer for building interior walls, characterized in that, The material comprises the bentonite-based functional material as described in claim 5, and an interior wall base material, wherein the mass ratio of the bentonite-based functional material to the interior wall base material is 15:85 to 40:60, and the coating thickness of the functional layer is 2 to 5 mm.
10. The moisture-retaining and antibacterial functional layer for building interior walls according to claim 9, characterized in that, The building interior wall base material is any one of water-based acrylic paint, diatomaceous earth paint, cement-based putty, or gypsum-based putty.